Stability of a Bose-condensed mixture on a bubble trap - Andriati, Alex; Brito, Leonardo; Tomio, Lauro [UNESP]; Gammal, Arnaldo (American Physical Society (APS), 2021)
Stability and the dynamical behavior of binary Bose-Einstein condensed mixtures trapped on the surface of a rigid spherical shell are investigated at the mean-field level, exploring the miscibility with and without vortex charges and considering repulsive and attractive interactions. To compute the critical points for stability, we follow the Bogoliubov-de Gennes method for the analysis of perturbed solutions, with the constraint that initially the stationary states are in a complete miscible configuration. For the perturbed equal-density mixture of a homogeneous uniform gas and when hidden vorticity is verified, with the species having opposite azimuthal circulation, we consider a small perturbation analysis for each unstable mode, providing a complete diagram with the intra- and interspecies interaction role on the stability of the miscible system. Finally, beyond small-perturbation analysis, we explore the dynamics of some repulsive and attractive interspecies states by full numerical solutions of the time-dependent Gross-Pitaevskii equation.